BRIDGING FINANCIAL AND DIGITAL COMPETENCES WITH INVESTMENT RISK THROUGH THE MEDIATING POWER OF INFORMATION DISCLOSURE - Elizabeth Sastrina Indrasari; Abdul Mukti Soma (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Digital technologies are changing rapidly, and this has changed the financial services industry, especially how people decide where to invest their money. This study looks at how digital literacy, financial literacy, and fear of missing out (FOMO) affect how much risk young investors are willing to take when investing with information disclosure as a mediating variable. The research data is taken from 447 investors of Gen Y and Z in West Java and used Partial Least Squares-Structural Equation Modeling (PLSSEM). The results show that being financially literate makes people more likely to search for financial information, but it also makes them less willing to take risks when investing. This suggests that people who know a lot about money are more careful when they invest. On the other hand, FOMO has a positive effect on both information searching and risk tolerance, showing how emotions can affect people online. Digital literacy helps people be more willing to take risks, but it does not have a big effect on how much information they search. These results show how important cognitive and emotional factors are in determining how people act when it comes to IT-driven finances. The study helps with responsible digital transformation by showing how important it is for individuals to be ready to navigate fintech ecosystems. It also gives regulators, platform providers, and educators ideas on how to promote more informed and resilient investment practices.